Behavioral activation for depression in patients with advanced cancer: study protocol for a multicenter randomized controlled trial - Takatoshi Hirayama; Yuko Ogawa; Asao Ogawa; Emi Igarashi; Saaya Soejima; Kotone Hata; Yusuke Utsumi; Yuki Mashiko; Kyoka Ogata; Ayako Kayano; Yuko Yanai; Shin-ichi Suzuki (BMC Cancer, 2023)
Abstract Background Though behavioral activation (BA) has been shown to be effective for depression, evidence in patients with advanced cancer has not been established. This study aimed to examine the effectiveness of a BA program on depression in this population. Methods A randomized controlled trial with a wait-list control group (waiting group) of 38 patients with advanced cancer and depression will be conducted at three sites in Japan. The BA program consists of seven sessions. Outcome measures will be evaluated at three times in the intervention group; at the entry, at the end of the intervention and 4 months after the end of the intervention and four times in the waiting group: at the entry, before the intervention, at the end of the intervention, and 4 months after the end of the intervention. Primary outcome is Beck Depression Inventory-II (BDI-II) score. To examine the main effect of the intervention, two-way repeated measures analysis of variance (ANOVA) will be conducted, with timing and intervention status as the independent variables and BDI-II score as the dependent variable. One-way repeated measures ANOVA will be conducted to combine data from the intervention and control groups and examine changes in BDI-II scores by timing in both groups. Secondary endpoints (anxiety, quality of life, spirituality, degree of behavioral activation, value, and pain) will be evaluated with rating scales. Two-way repeated measures ANOVA will be conducted to examine whether there are differences between the groups before and after the intervention, with timing and intervention status as the independent variables and scores on each rating scale as the dependent variables. Discussion This multicenter randomized controlled trial is the first study to assess the effectiveness of BA on depression in patients with advanced cancer. Our findings will provide evidence about the effectiveness of BA on depression and provide an intervention option that is acceptable and feasible for the treatment of depression in this population. The results of this study will lead to improved mood and rebuilding to regain life purpose and value in this vulnerable population. Trial Registration Number jRCT, jRCT1030210687, Registered 22 March 2022, https://jrct.niph.go.jp/en-latest-detail/jRCT1030210687 .